2014
DOI: 10.3762/bjoc.10.180
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of thiol-modified phenol derivatives for the use in thiol–ene photopolymerizations

Abstract: SummaryThiol–ene photopolymerizations gain a growing interest in academic research. Coatings and dental restoratives are interesting applications for thiol–ene photopolymerizations due to their unique features. In most studies the relative flexible and hydrophilic ester derivative, namely pentaerythritoltetra(3-mercaptopropionate) (PETMP), is investigated as the thiol component. Thus, in the present study we are encouraged to investigate the performance of more hydrophobic ester-free thiol-modified bis- and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…For example to achieve better flexural strength ester free multifunctional thiols derived from an array of bisphenol structures were used. 37 Such materials showed also an improved performance in relation to PETMP/TTT after conditioning in water for 24 hours. Other reports described the use of ester-free thiol-ene materials as dental resins.…”
Section: Resultsmentioning
confidence: 98%
“…For example to achieve better flexural strength ester free multifunctional thiols derived from an array of bisphenol structures were used. 37 Such materials showed also an improved performance in relation to PETMP/TTT after conditioning in water for 24 hours. Other reports described the use of ester-free thiol-ene materials as dental resins.…”
Section: Resultsmentioning
confidence: 98%
“…The characterization of photocured thiol‐ene networks has mainly been focused on the structural parameters related to ene flexibility in the past . Although there are some reports describing the effect of different thiol monomers on the cured network, most of them deal with mercapto propionic acid derivatives such as PETMP, TMPMP, or pentaerythritol tetrakis (mercaptobutylate) . Basically, it is well documented that thermal and mechanical properties directly correspond to features inherent to the chemical structure of the ene and thiol monomer.…”
Section: Resultsmentioning
confidence: 99%
“…Although there is a vast number of studies describing the effect of different enes on the physicochemical properties of thiol‐ene polymers, there are only a few reports, which deal with alternative thiol compounds and their impact on the polymeric properties . Very recently, the group of Bowman and coworkers successfully demonstrated the beneficial behavior of ester‐free thiols based on the example of tetra(2‐mercaptoethyl)silane.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that the mechanics of the flexible step-growth polymer backbone containing soft sulfide linkages can be enhanced significantly in poly(thioether) networks by eliminating the presence of esters [3033]. Achieving that, and combining other benefits of step-growth processes has led us toward revisiting the thiol-ene concept for dental composite applications.…”
Section: Introductionmentioning
confidence: 99%